Living through continuous displacement: Resisting homeless identities and remaking precarious lives. Issue 116 (November 2020) - Preece, Jenny; Garratt, Elisabeth; Flaherty, Jan
Highlights: This paper explores the identities of individuals experiencing homelessness. We use the framing of 'continuous displacement' to reflect experiences of precarity. Individuals resisted homeless identities, maintaining a 'normal', housed, identity. Participants tried to distance themselves from the stigma of homelessness. Some reclaimed precarious identities as a source of value, denied by homelessness. Abstract: This article considers how individuals who experience continuous displacement from housing manage the 'spoiled identity' of homelessness. The research draws on in-depth, biographical interviews with 39 individuals living in Oxford, a high-cost UK city. All had experienced forms of homelessness in the previous three years. Building on critical debates around experiences of precarity in urban geography, the article explores how individuals construct and maintain a sense of identity whilst living precarious lives. Participants were constantly confronted with their own precarity in pressured housing markets, which fostered their displacement, and then undermined re-entry into stable housing. Yet, participants described their attempts to maintain a 'normal' life, rejecting homeless subjectivities as they anchored their identity to daily practices of self care. These were also a key means of distinction from others experiencing displacement, enabling individuals to dis-identify from those characterised by moral and personal failings, thus highlighting their own responsibility and resourcefulness. Others described the bodily transformation that was associated with assuming the identity of 'homeless'. Participants moved between different subject positions, with distinct narratives through which individuals sought to reclaim precarious identities, foregrounding alternative choices, pride in survival and resourcefulness, and freedom. Whilst this occurred within a context of extreme constraint, individuals were actively engaged in attempts to construct a sense of worth and value that was denied by a 'homeless identity'. The article contributes to contemporary debates foregrounding social processes in understandings of the lived experiences of marginalisation, as well as adding empirical depth to representations of hidden homelessness.